CONTROLLING EXAMOPHOBIA AMONG COLLEGES OF EDUCATION STUDENTS USING ASSERTIVENESS TRAINING AND COGNITIVE RESTRUCTURING - Babatunde, Saka Ibrahim; Kadiri, Hassan (Sanata Dharma University Yogyakarta, 2026)
This study examined the effectiveness of assertiveness training and cognitive restructuring on examophobia among Colleges of Education students in Kwara state. The study adopted quasi experimental research design with pretest, posttest, non-randomized and non-equivalent control group of 3x2x2 factorial design. The experimental groups were exposed to assertiveness training and cognitive restructuring treatments while the control group was taught using the lecture method. The instruments used for data collection were Examination Phobia Scale and Adapted Study Habits Inventory while descriptive statistics, and ANCOVA were used to analyze data. The study revealed that cognitive restructuring and assertiveness training were effective techniques for treating examophobia. However, students’ gender and study habits were not determinants in the effectiveness of cognitive restructuring and assertiveness training techniques in treating examophobia. Also, the study found that there was no significant interaction effect of gender, study habits and treatments on examophobia among students. Therefore, the study recommended the establishment of modern student counselling and human development centres in the Colleges of Education.